KORELASI KEDISIPLINAN BELAJAR TERHADAP HASIL BELAJAR PPKN KELAS IX B SMPIT AL-MUMTAZ PONTIANAK - Ashari, Ashari; Bistari, Bistari; Purnama, Shilmy; Imran, Imran; Utami, Tri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research seeks to explore the link between learning discipline and academic outcomes for students in PPKn (Civics Education). A quantitative approach using a correlational method is utilized. Data sources include PPKn teachers and students, with data collection techniques consisting of questionnaires, PPKn test results, and documentation. The research follows several stages of data analysis, including descriptive statistical analysis, normality test, linearity test, hypothesis testing, and determination coefficient test, followed by drawing conclusions. To examine the relationship between learning discipline and academic performance in PPKn, the researcher distributed questionnaires and collected students' academic results from the PPKn teacher. Subsequently, normality and linearity tests were conducted, followed by a Pearson Product-Moment correlation test. Using SPSS 16, the data was evaluated to explore the link between the two variables. The outcomes revealed a significance value of 0.102, higher than 0.05, reflecting no significant correlation among learning discipline and students' academic performance in PPKn for Class IX B at SMPIT Al-Mumtaz.